CCBC Choices: 2005 - Horning, Kathleen T.; Lindgren, Merri V.; Rudiger, Hollis; Schliesman, Megan (Friends of the CCBC, Inc., 2005)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children’s Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 2005 recommends 231 titles for children and young adults published in 2004. It includes a commentary on the 2004 publishing year, including statistics on the number of books by and about people of color published for children and teens.
Keywords: Bibliographies; Children's Literature; Young Adult Literature; Cooperative Children's Book Center